Analysis of Interest in Getting Married and Having Children in Digital Generation Adolescents: A Case Study of Pabelan Sukoharjo Village Community Indonesia - Aliyah Rizkika Hendriansyah; Diva Amelia Octaviana; Nabila Riyadi; Nada Salsabila; Nafisah Nafisah; Syifa’ Al Atsariyah; Salsabilla Adzahra; Sofia Bayu Estetika; Febryan Hidayat; Nur Utomo Bayu Aji (Walidem Institute and Publishing, 2024)
The purpose of this study is to uncover and analyze the interest in getting married and having children in digital generation adolescents. This research method uses qualitative research and literature review, while the approach uses phenomenology, social, and normative. The data source used interviews with an online questionnaire spread. The object of research was conducted in Pabelan village, Sukoharjo, Indonesia. The results revealed that in the last 10 years, it has been known that interest in marriage in Indonesia has decreased due to several triggering factors that make the low percentage of productive generations in the future, thus having a positive and negative impact. Interest in getting married and having children in the digital generation in the Pabelan area, Sukoharjo, Indonesia is relatively stable and there is no significant decline. The conclusion of this journal shows that the interest in getting married and having children in the digital generation adolescents is influenced by technology and current developments as well as rampant conflicts that occur in the household.